Synergism and antagonism of influence low dose radiation and environment on health of population in Ukraine - Dikiy, N.P.; Medvedeva, E.P. (Вопросы атомной науки и техники, 2019)
The genesis of carcinogenic diseases is characterized by a multifactor dependence. The effect of low dose radiation in combination with environmental factors has a significant number of features. It was studied the influence of certain features of the environment and the mental state of the person (affect) on the development of the incidence of carcinogenic diseases of the population in Ukraine. Given the various adverse environmental conditions, the effect of radiation in low doses can be enhanced or weakened. Synergism and antagonism of the effect of low dose radiation and environment on the health of the population are discussed. Виникнення канцерогенних захворювань характеризується багатофакторною залежністю. Вплив малих доз радіації в поєднанні з факторами навколишнього середовища має значну кількість особливостей. Було вивчено вплив деяких особливостей навколишнього середовища і психічного стану людини (афекту) на розвиток захворюваності канцерогенними хворобами населення України. Виявлено залежність захворюваності канцерогенними хворобами від природних і побутових умов населення. Обговорюються також синергізм і антагонізм впливу малих доз радіації і різних екологічних факторів на розглянуті параметри. Возникновение канцерогенных заболеваний характеризуется многофакторной зависимостью. Влияние малых доз радиации в сочетании с факторами окружающей среды имеет значительное количество особенностей. Было изучено влияние некоторых особенностей окружающей среды и психического состояния человека (аффекта) на развитие заболеваемости канцерогенными болезнями населения Украины. Выявлена зависимость заболеваемости канцерогенными болезнями от природных и бытовых условий населения. Обсуждаются также синергизм и антагонизм влияния малых доз радиации и различных экологических факторов на рассматриваемые параметры.